A comprehensive review on the usage of the nano-sized particles along with diesel/biofuel blends and their impacts on engine behaviors. (1st May 2023) - Gad, M.S.; Ağbulut, Ümit; Afzal, Asif; Panchal, Hitesh; Jayaraj, S.; Qasem, Naef A.A; El-Shafay, A.S.
Highlights: Investigated nanoparticle usage along with diesel/biofuel blends. Noticed a significant improvement in engine performance and emission characteristics with nanoparticles. Observed some critical problems with nanoparticle usage in fuels. Accelerated chemical reactions during the combustion process with the presence of nanoparticles in the combustion chamber. Abstract: Global warming, climate change, air pollution, and harmful exhaust emissions for human health are highly associated with the burning of petroleum fuels at a huge level. In the beginning, biodiesel fuels have been introduced as a promising alternative fuel to mitigate these problems. However, poor atomization, low energy content, high viscosity, and density of biodiesels are the main obstacles to the frequent usage of biodiesel fuels in diesel engines. That is because biodiesel fuels in CI engines have generally resulted in higher fuel consumption, lower thermal efficiency, and higher NOx emission. On the other hand, most fuel researchers recently announced that the addition of nanoparticles in biodiesel blends has led to making biodiesels attractive again by significantly improving their poor biodiesel properties such as thermophysical properties, calorific value, heat transfer rate, evaporation rate, etc. From this point of view, many published papers in the area demonstrated that the addition of nanoparticles in biodiesel blended fuels has simultaneously provided fewer exhaust emissions, better performance, and combustion characteristics thanks to the high catalyst effect of nanoparticles. In the conclusion, the present review paper clearly announced that the addition of nanoparticles is a very strong way to re-improving the worsened engine combustion, performance, and emission characteristics of biodiesel-diesel blends.